Paradigma Baru Pemikiran Dakwah Islam - Sarbini, Ahmad (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2010)
In daâwah perspective, the efforts to do social transformationis not enough only rely on conventional paradigm. In its reality, the paradigm have minus attention to develop consciousness by society and tend doing exploitation to daâi interest that daâi position kineer keen daâi delightedÂ in, the greater great its advantages only for daâi not for umat. This paradigm must be changedÂ by placement daâi as facilitator for axchanging and supported by movement pattern that combine appreciation and emforcing vis a vis between Islamic value and cultural values and wary increasion of world isme that continuing dynamicÂ process.